FY2019 : Output Cost Estimates and Budget Outturn. - International Monetary Fund. Office of Budget and Planning (Washington, D.C. : International Monetary Fund, 2019)
The paper presents highlights from the FY 19 budget, followed by a discussion of outputs based on the Fund Thematic Categories and of inputs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet